2021
DOI: 10.3748/wjg.v27.i40.7000
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal and hepatic involvement during COVID-19 pandemic: A focus on pediatric population and possible future implications

Abstract: Since the coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has rapidly spread worldwide, there is still limited knowledge about this condition and its natural history. Children have been relatively spared during COVID-19 pandemic but a novel syndrome known as multisystem inflammatory syndrome (MIS-C) has emerged, following a SARS-CoV-2 infection in children and adolescents. This syndrome can lead to shock and multiple organ failure requiring in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In that study, the authors showed that intranasal or gastric inoculation with SARS-CoV-2 induced infections and pathologic changes not only in respiratory tissues but also in digestive tissues[ 7 ]. In a recent letter to the World Journal of Gastroenterology ( WJG ) editor[ 8 ], Sica et al [ 8 ] contended that GI and hepatic involvement are the most common presenting symptoms of COVID-19 and multisystem inflammatory syndrome recently described in children and adolescents. This syndrome can lead to shock and multiple organ failure requiring intensive care[ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In that study, the authors showed that intranasal or gastric inoculation with SARS-CoV-2 induced infections and pathologic changes not only in respiratory tissues but also in digestive tissues[ 7 ]. In a recent letter to the World Journal of Gastroenterology ( WJG ) editor[ 8 ], Sica et al [ 8 ] contended that GI and hepatic involvement are the most common presenting symptoms of COVID-19 and multisystem inflammatory syndrome recently described in children and adolescents. This syndrome can lead to shock and multiple organ failure requiring intensive care[ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A liver biopsy was performed in two children who showed parenchyma inflammation with lymphocytic portal, as well as the bile duct proliferations. All three children were provided with a steroid treatment, which resulted in liver enzyme improvement and overall successful therapy [80].…”
Section: Multisystem Inflammatory Syndrome In Children (Mismentioning
confidence: 99%
“…Gastrointestinal (GI) symptoms are the main extra‐pulmonary manifestations of COVID‐19, such as diarrhea, vomiting, and abdominal pain, and the incidence is between 40% and 60% 110,111 . The prevalence of GI symptoms in female patients was significantly higher than in male patients 112 .…”
Section: Manifestations Of Long Covid In Multiple Organsmentioning
confidence: 99%